Avaliação da cicatrização da pele de rato wistar após múltiplas sessões de terapia fotodinâmica - Angarita, Dora Patricia Ramírez (2012)
Nonmelanoma skin cancer is the most frequent disease in the world population and it is becoming a public health problem. Due to this fact, new technologies are being tested for the treatment of this disease. Photodynamic Therapy (PDT) is a noninvasive technique with an excellent cosmetic outcome, well tolerated by patients and with good healing results when used for the initial stages of cancer lesions. PDT uses molecular oxygen, light at appropriate wavelengths and the drug photosensitizers to generation of reactive oxygen species such as singlet oxygen responsible for the photoinactivation of target cells. The characteristics of scar tissue after multiple sessions of PDT is not completely understood. It is not known whether multiple sessions of PDT may cause irreversible changes in the treated tissue. Thus, the present study has as its main objective the evaluation of the characteristics of the skin scarred after multiple sessions of PDT. For this study, we used 25 Wistar type male mice. These 25 mice were grouped into 5 subgroups of 5 each: G0, control group, non-subjected to any treatment; G1, exposed to one PDT session and after, there was made a lesion with CO2 laser over the scarred tissue; G2, the group is submitted twice for the same procedure, G3, subjected to 3 times the procedure performed for G1 group; G4, exposed to 4 times the procedure. Once the mice s skin was healed, we performed macroscopic and microscopic evaluations of the histological pieces. Furthermore, we made a microscopic evaluation of collagen fibers and the generation of the second-harmonic through multiphotons microscopy. Macroscopically, it was observed a good healing for the different groups. The aesthetic result showed a decrease after the third and fourth sessions. In the microscopic study, it was observed an conservation of the quantity of sebaceous glands per square millimeter (mm2). The morphology of collagen fibers when evaluated using two-photon excited fluorescence in the confocal microscope, showed thinner fibers with a parallel arrangement and lower density in the G3 e G4 compared to the control group. It was not observed decrease in the generation of second harmonic in histopathology slides. These results suggest that healing in skin after four (4) sessions of PDT/lesion presents alterations in aesthetic and histological of the morphology of collagen fibers that may be related to submitted of the skin in eight (8) consecutive occasions with an incomplete healing between them.